2013
DOI: 10.1136/gutjnl-2013-305279
|View full text |Cite
|
Sign up to set email alerts
|

Individualised therapy is more cost-effective than dose intensification in patients with Crohn’s disease who lose response to anti-TNF treatment: a randomised, controlled trial

Abstract: NCT00851565.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
329
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(348 citation statements)
references
References 26 publications
4
329
0
9
Order By: Relevance
“…Two were randomized controlled trials [14,18], and five used a modeling approach (three used a Markov model [16,17,19] and two a discrete event model [20,22]). Four studies included only CD patients [18][19][20]22], one included both CD and UC patients [14], and two only RA patients [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Two were randomized controlled trials [14,18], and five used a modeling approach (three used a Markov model [16,17,19] and two a discrete event model [20,22]). Four studies included only CD patients [18][19][20]22], one included both CD and UC patients [14], and two only RA patients [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Secondary loss-of-response to infliximab was defined as recurrence of active disease with a Crohn's disease activity index (CDAI) C220 and/or a minimum of one draining perianal fistula. In a prior publication, the authors reported superior economic outcomes and similar clinical outcomes for the TDM-based intervention arm versus the doseescalation arm at week 12 [5]. Here, the authors provide longer follow-up and report that cost savings are maintained throughout week 20 and the first year of follow-up, with similar clinical outcomes observed in both groups.…”
mentioning
confidence: 50%
“…Although the threshold drug concentration of 0.5 lg/ml is generally considered to be low, using higher thresholds made no difference according to a sensitivity analysis included in their original publication [5]. Nonetheless, an objective measure could have been used to confirm disease activity in the subpopulation of patients with ''adequate'' drug exposure, since the recommended TDM-based intervention for overcoming loss-ofresponse in this subgroup was to change to a different class of therapy, a consequential decision due to the limited salvage options available.…”
mentioning
confidence: 99%
“…Further, dose optimization can reduce over-and under-treatment. Greater understanding of pharmacokinetics is leading to individualized drug dosing that is cost saving and clinically efficient [118,119]. Furthermore, targeting objective disease outcomes also improves effective drug dosing and costeffectiveness [120].…”
Section: Pharmacoeconomic Considerations Of Biological Therapymentioning
confidence: 99%